Desoxigenação catalítica em processo contínuo e semibatelada para obtenção de bioquerosene de aviação - Araújo, Pedro Henrique Moraes de (2019)
Pollution and greenhouse gas emissions from fossil fuels are increasingly recurring themes. As an alternative and efficient way, through renewable energy resources, the aviation industry makes an intense search for the ideal sustainable biofuel in order to reduce the sector's CO2 emissions. There are already certified methods for obtaining alternative fuels, however they can be optimized as well as embrace other feedstocks to reduce production and logistics costs. Given this scenario, this research aimed to evaluate the semi-batch catalytic deoxygenation processes for microalgae Scenedesmus acuminatus and licuri oils using Pd/C catalyst, as well as to optimize the reaction conditions of the continuous process for these raw materials application, aiming to obtain n- alkanes in the biojet fuel range. For the continuous process, in a trickle-bed reactor, granular Pd/C catalysts were prepared and compared to commercial ones. As results, Scenedesmus acuminatus microalgae oil obtained 82.9% conversion, with 36.6% yield for n-alkanes, using 1% Pd/C catalyst in the semi-batch reactor. For the licurisource, the semi-batch reaction using 5% Pd/C catalyst achieved n-alkanes yielding up to 39.2% for biodiesel and 80.7% selectivity for oil deoxygenation. For the continuous reactor, the ideal reactant concentration found was 20 wt.%. Further, increasing the carbon chain length facilitates the continuous bed deoxygenation process. The fatty acids showed the best results for conversion and selectivity. The lab-prepared 5% Pd/C granular catalyst showed better yield (52.4%) and conversion (57.0%) to esters than the 1% Pd/C SigmaAldrich catalyst. The commercial catalyst showed better selectivity to n-alkanes (93.1%). The licuri biodiesel reaction yielded 52.4% yield with conversion of 57.0% and selectivity to n-alkanes up to 93.1%. The CO2 selectivity in general indicated the catalysts favoring by decarboxylation pathway, considering the loss of a carbon in the n-alkanes of reaction products.